Sensibilização dependente de tempo em paulistinhas adultos como modelo de transtorno de estresse pós-traumático: papel do óxido nítrico - LIMA, Monica Gomes (Universidade Federal do Pará, 2017)
Post-traumatic stress disorder (PTSD) is classified as a trauma- and stressor-related disorder, a set of severely debilitating neuropsychiatric disorders characterized by the disregulation of stress responses after a traumatic event. Zebrafish (Danio rerio Hamilton 1822) emerged as an important model organism for the study of genetic, neuropharmacological and behavioral functions, such as the study of anxiety and stress. Nitric oxide (NO) is a gaseous transmitter that appears to have an important role in the regulation of neurobehavioral responses to stresss, including in zebrafish. In this scenario, we propose a behavioral model for PTSD in the evaluation of the time-dependent sensitization of behavior in zebrafish as a consequence of the exposure to conspecific alarm substance (AS) – a potent stressor. Using this model, we will verify the role of the nitrergic system in this process of sensitization. Animals will be exposed to AS and kept stress-free for 24 h; after this interval, animals' behavior will be analyzed. 5 experiments will be made to investigate: i) the delayed effect of alarm substance on different behavioral tasks in zebrafish, ii) a comparison of time-dependent sensitization on shortfin and longfin phenotypes; a comparação da sensibilização dependente de tempo nas linhagens shortfin e longfin, iii) the application of Behavioral Cutoff Criteria on timedependent sensitization, iv) the quantification of extracellular glutamate and tissue nitrite in the telencephalon after exposure to alarm substance, and v) the participation of NO on the initiation and consolidation of time-dependent sensitization. Our results revealed that: i) alarm substancce produces a delayed sensitization of anxiety (increased geotaxis, decreased habituation, increased erratic swimming and thrashing in the novel tank test; decreased time on white, increased erratic swimming, risk assessment and thigmotaxis on the ligh/dark test) and arousal (increased swim distance on the first trial and increased habituation slope in the startle reactivity test). ii) In relation to shortfin animals, exposure of longfin zebrafish to AS sensitized time on white, risk assessment and thigmotaxis more, while shortfin animals had more erratic swimming. Iii) 25.74% of AS-exposed animals reached criteria for Extreme Behavioral Response (EBR), and 20% reached criteria for Minimal Behavioral Response VII (MBR); in non-exposed animals, only 4% reached criteria for EBR and 96% reached criteria for MBR. Animals classified as EBR spent less time in the white compartment, with shorter entries, more thigmotaxis and more erratic swimming than animals classified as MBR and non-exposed controls. iv) treatment with L-NAME 30 minutes before AS exposure did not block the behavioral sensitization in the light/dark test; v) treatment with L-NAME 30 minutes after AS exposure blocked the sensitization of scototaxis and risk assessment; vi) treatment with L-NAME 90 minutes after AS exposure blocked the sensitization of risk assessment, erratic swimming and thigmotaxis. Theses results suggest that time dependent sensitization is a good model to study PTSD and point to NO as a important mediator in this process.